EFFECT OF DEPRIVATION ON PRODUCTIVE TRAITS OF NEWLY HATCHED CHICKS: HISTOPATHOLOGICAL STUDY - Kh. Jalob, Z. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The aim of this study was to investigate the effect of deprivation on productive traits of newly post hatched chicks. A total number of Ross 308 birds (120) were divided into four groups as in the following way: group1 (G1=38 bird), was regarded as positive control and had been supplied directly with the feed, whereas group2 (G2=27 bird), group3 (G3=28 bird) and group4 (G4=27 bird) were supplied with the diet at post hatch period of 24h, 48hr and 72h respectively. Water supplied was ad libitum to all groups immediately after placing. Result revealed that G1 showed significant performance (P